ABC Transporter Genes Show Upregulated Expression in Drug-Resistant Clinical Isolates of Candida auris: A Genome-Wide Characterization of ATP-Binding Cassette (ABC) Transporter Genes - Wasi, Mohd; Khandelwal, Nitesh Kumar; Moorhouse, Alexander J.; Nair, Remya; Vishwakarma, Poonam; Bravo Ruiz, Gustavo; Ross, Zoe K.; Lorenz, Alexander; Rudramurthy, Shivaprakash M.; Chakrabarti, Arunaloke; Lynn, Andrew M.; Mondal, Alok K.; et al. (Frontiers in Microbiology, 2019)
ATP-binding cassette (ABC) superfamily members have a key role as nutrient importers and exporters in bacteria. However, their role as drug exporters in eukaryotes brought this superfamily member to even greater prominence. The capacity of ABC transporters to efflux a broad spectrum of xenobiotics represents one of the major mechanisms of clinical multidrug resistance in pathogenic fungi including Candida species. Candida auris, a newly emerged multidrug-resistant fungal pathogen of humans that has been responsible for multiple outbreaks of drug-resistant infections in hospitals around the globe. Our study has analyzed the entire complement of ABC superfamily transporters to assess whether these play a major role in drug resistance mechanisms of C. auris. Our bioinformatics analyses identified 28 putative ABC proteins encoded in the genome of the C. auris type-strain CBS 10913T; 20 of which contain transmembrane domains. Quantitative real-time PCR confirmed the expression of all 20 transmembrane domain transporters, underlining their potential in contributing to the C. auris drug resistant phenotype. Changes in transcript levels after short-term exposure of drugs and in drug-resistant C. auris isolates suggested their importance in the drug resistance phenotype of this pathogen. CAUR_02725 orthologous to CDR1, a major multidrug exporter in other yeasts, showed consistently higher expression in multidrug-resistant strains of C. auris. Homologs of other ABC transporter genes, such as CDR4, CDR6 and SNQ2, also displayed raised expression in a sub-set of clinical isolates. Together, our analysis supports the involvement of these transporters in multidrug resistance in C. auris.